Changes in breaststroke swimming performances in national and international athletes competing between 1994 and 2011 - a comparison with freestyle swimming performances - Wolfrum, M.; Rüst, C.; Rosemann, T.; Lepers, R.; Knechtle, B. (BMC Sports Science, Medicine and Rehabilitation, 2014)
The purpose of the present study was to analyse potential changes in performance of elite breaststroke swimmers competing at national and international level and to compare to elite freestyle swimming performance.